Regional differences in high K+-/tyramine-evoked releases of aromatic amine neurotransmitters/metabolite in the rat caudate putamen - del Fierro, Ramon S. (Animo Repository, 1998)
Each region of the caudate putamen shares a common architectural and neurochemical features and afferent connectivities although they differ to various extents in the type of topological distribution of their afferents/efferents and circuitries. As a matter of fact, the dopaminergic innervation of the caudate putamen is both anatomically and neurochemically heterogeneous, the axom terminals being from several groups of mesencephalic cell bodies in the A8/A9 and A10 regions. Hence in the light of the established anatomical and biochemical differences, it is also possible that heterogeneity also exists in the dynamic release processes of the aromatic amine neurotransmitters/metabolites, or its control within the caudate putamen. In this study, the in vivo mocrodialysis technique was used to examine the basal extracellular levels, and high potassium (100mM) depolarization/tyramine (50 μM)-included releases of dopamine (DA). Serotonin (5-HT), norepinephrine (NE), 3,4-dihydroxyphenilacetic acid (DOPAC), 5- dihydroxyphenilacetic acid (5-HIAA), and homovanillic acid (HVA) in various regions of the caudate putamen spanning antero/posterior and medio/lateral axis. Solutions containing normal ringer, high potassium ringer and tyramine were perfused at a rate of 2 μL/min to the desired regions appropriately installed with a U-shaped microdialysis probe (1 mm); and 60 μL dialysates were analyzed by an HPLC/ECD system (0.1 M sodium acetate, 0.1 mM EDTA 2Na, 5% methanol, pH 5.02; 0.55V; 28oC). Perfusion of high potassium ringer solution (60 min) elicited an increased released of aromatic neurotransmitters and a corresponding marked reduction in the metabolites. On the other hand, perfusion of tyramine (60 min) resulted in a drastic increase of DA and DOPAC. In both cases, the highest response was exhibited at the antero-medial caudate putamen.